Kajian Perbandingan dan Preferensi Masyarakat Terhadap Kualitas Pelayanan Transportasi Online dan Konvensional di Kota Jayapura: (Civitas Akademika di Lingkungan Kampus Universitas Cenderawasih) - Marlon Wanane; Sudiro Sudiro; Riano M. Rumbiak (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
In this modern era, people have various activities and to fulfill these activities, people need transportation as a supporting tool/assistant tool in carrying out their activities. Therefore, transportation service entrepreneurs are competing to attract the interest of their consumers by improving services, ease of ordering, fleet comfort, punctuality and so on. In Indonesia, there are many types of transportation that also function as public transportation, namely transporting people/goods and collecting agreed fees. The general public is currently familiar with two types of transportation, namely application-based online transportation and conventional transportation. Where application-based online transportation is the transfer of goods and people from place of origin to destination. The current flow of technological developments is something that must be understood and whether we like it or not, we must keep up with the flow of technological developments, so that the emergence of application-based online transportation is a transportation service that takes advantage of technological developments. Conventional transportation is passenger transportation carried out on a rental basis. Conventional transportation, for example, includes buses, public transportation, taxis, pedicabs and motorbike taxis. In line with current developments, the existence of conventional transportation is gradually being replaced by the choice of more sophisticated modes of transportation with the use of technological advances such as the emergence of application-based online transportation. Apart from being time efficient, online transportation itself can also be used at an affordable cost. However, this is different with conventional types of transportation, not all of which can be reached easily, sometimes you have to wait for a long time to be able to access or use these transportation services. Using Comparative Analysis The use of Comparative Analysis aims to compare the differences in services between two types of online and conventional transportation modes based on the type of transportation mode and the services provided by service providers to users such as the Academic Community located on the Cenderawasih University campus environment. By using Descriptive Statistical Analysis the data that has been collected can be analyzed by calculating the average perception of user respondents regarding service quality preferences for two types of online and conventional transportation modes from the Academic Community in the Cenderawasih University Campus environment.